Identification of bacterial contaminants from calcium carbonate filler production lines and an evaluation of biocide based decontamination procedures. Issue 4 (21st April 2017) - Odić, Duško; Prah, Jana; Avguštin, Gorazd
Abstract: The aim of this study was to analyze the bacterial community in the production line of a calcium carbonate filler production company and to investigate possible causes for bacterial presence. Throughout 2012, 24 carbonate slurry and six groundwater samples were analyzed. Pseudomonas and Microbacterium were the most frequent contaminants in the slurry, whereas Pseudomonas and Brevundimonas dominated the groundwater samples. Of the 43 different bacterial strains isolated, only five were found both in the slurry and the groundwater, indicating that the latter was not a major source of contamination. The efficacy of 54 commercial biocidal formulations was tested against an artificial bacterial consortium composed of selected slurry isolates. A formulation containing 7.5–15% (v v –1 ) bronopol and 1.0–2.5% (v v –1 ) [chloroisothiazolinone (CIT) + methylisothiazolinone (MIT)] exhibited the highest efficacy. Of the possible causes for bacterial presence, sporogenesis and biocide adsorption to carbonate particles were found to be less probable compared to bacterial adsorption to particles, and the acquisition of resistance to biocides.